Religulous [videorecording (DVD)] - Charles, Larry, 1956-; Maher, Bill (Lionsgate, 2009)
Comedian and TV host Bill Maher takes a pilgrimage across the globe on a mind-opening journey into the ultimate taboo: questioning religion. Meeting the high and low from different religions, Maher asks questions, like 'Why is faith good?' and more.